Prediction of Groundwater Storage in Gabus Wetan Subdistrict, Indramayu Regency, West Java Province, Indonesia - Saputra, Septian Fauzi Dwi; Waspodo, Roh Santoso Budi; Setiawan, Budi Indra (Departemen Teknik Sipil dan Lingkungan IPB, 2016)
Gabus Wetan Subdistrict, Indramayu Regency in West Java Province known as one of rice production center in Indonesia has common problem of surface irrigation water that is unavailable in dry season. It necessary to find alternative water source from groundwater to increase intensity as well as productivity. The aim of this study were to determine geoelectrical-hydrogeological profiles in form of distribution characteristics of the aquifer indicated by the resistivity of rocks and to predict the groundwater reserve potential in Gabus Wetan, Indramayu Regency. Resulted information can then be used to exploit groundwater for alternative supply of irrigation water. The result of this study shown that the rock resistivity in the area ranging between 1-30 Ωm. The rock aquifers consist of sandy clay, clayey sand, and sand. The shalllow groundwater (unconfined aquifer) are in the range of 3-40 meters below the soil surface having tickness of aquifer in the range of 7-20 meters. The deep groundwater (confined aquifer) can be estimated at the depth of more than 60 meters below the soil surface having tickness more than 40 meters. The hydraulic conductivity is estimated 20 m/day for unconfined aquifer and confined aquifer. The predicted groundwater storage of unconfined aquifer was about 31,687.2 m3/day or 0.37 m3/sec and confined aquifer 99,382.6 m3/day or 1.15 m3/sec.Keywords: aquifer, groundwater, hydrogeology, hydraulic conductivity, resistivity